Resistin Regulates Pituitary Lipid Metabolism and Inflammation In Vivo and In Vitro - F. Rodriguez-Pacheco; M. G. Novelle; M. J. Vazquez; E. Garcia-Escobar; F. Soriguer; G. Rojo-Martinez; E. García-Fuentes; M. M. Malagon; C. Dieguez (Mediators of Inflammation)
The adipokine resistin is an insulin-antagonizing factor that also plays a regulatory role in inflammation, immunity, food intake, and gonadal function and also regulates growth hormone (GH) secretion in rat adenopituitary cells cultures with the adipokine. Although adipose tissue is the primary source of resistin, it is also expressed in other tissues, including the pituitary. The aim of this study is to investigate the possible action of resistin on the lipid metabolism in the pituitary gland in vivo (rats in two different nutritional status, fed and fast, treated with resistin on acute and a chronic way) and in vitro (adenopituitary cell cultures treated with the adipokine). Here, by a combination of in vivo and in vitro experimental models, we demonstrated that central acute and chronic administration of resistin enhance mRNA levels of the lipid metabolic enzymes which participated on lipolysis and moreover inhibiting mRNA levels of the lipid metabolic enzymes involved in lipogenesis. Taken together, our results demonstrate for the first time that resistin has a regulatory role on lipid metabolism in the pituitary gland providing a novel insight in relation to the mechanism by which this adipokine can participate in the integrated control of lipid metabolism.